If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -18 = 7x Reorder the terms: -18 + 8x = 7x Solving -18 + 8x = 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -18 + 8x + -7x = 7x + -7x Combine like terms: 8x + -7x = 1x -18 + 1x = 7x + -7x Combine like terms: 7x + -7x = 0 -18 + 1x = 0 Add '18' to each side of the equation. -18 + 18 + 1x = 0 + 18 Combine like terms: -18 + 18 = 0 0 + 1x = 0 + 18 1x = 0 + 18 Combine like terms: 0 + 18 = 18 1x = 18 Divide each side by '1'. x = 18 Simplifying x = 18
| -700+200+20x=0 | | 14.3=1.1+3d | | 21.5=x/3 | | (2x+3)(x+1)=6x | | 7/4•3-2 | | 4x=284 | | 0.0305t^3-0.469t^2+1.705t+6.93=0 | | 3/4(2x-4)=x-19 | | x-24=63 | | 20x+5+21x+1=180 | | 35=27+4n | | 0.5x+x+20=276 | | x^2+y^2+12x-10y-2=0 | | x+21=x+57 | | (4x-3)(3x+3)=0 | | 54-17=n | | 8-2z=5 | | 5p+p=25.53 | | 2x+9=7+4x | | h(t)=8t^2+48t+8 | | 7x-70=3x+10 | | 2x+1(ln)3=27 | | -4+20=-4 | | 5/6x=-8/9 | | 3-5x=7x-141 | | 6x-3=4x-2-3x-6 | | 3x+12=2x+26 | | 2/k-6=28 | | 7(x+4)-3(x-5)=6 | | 42-3x=15 | | 1.3g+1.9=11.1 | | -3+5+-2= |